Deletion of the angiopoietin receptor Tie2 enhances proliferation and sprouting of cardiac endothelial cells - Anisimov, Andrey; Lackman, Madeleine H.; Augustin, Hellmut; Mervaala, Eero; Alitalo, Kari; Karaman, Sinem (Angiogenesis, 2026)
Endothelial cells (ECs) of the heart proliferate and form new vessels in response to vascular endothelial growth factor (VEGF), but VEGF has not benefited the therapy of cardiac ischemia because of its side effects. Here, we explored if deletion of the vascular steady-state homeostasis maintaining Tie1 and Tie2 receptor tyrosine kinases affects the proliferation and sprouting of cardiac ECs.